2014
DOI: 10.5145/acm.2014.17.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Characterization ofSalmonellaspp. Clinical Isolates in Gyeongsangbuk-do Province, 2012 to 2013

Abstract: Background: Extended-spectrum cephalosporins and fluoroquinolones are important antimicrobials for treating invasive salmonellosis, and emerging resistance to these antimicrobials is of paramount concern. Methods: A total of 30 Salmonella spp. clinical isolates recovered in Gyeongsangbuk-do from 2012 to 2013 were characterized using antibiotic resistance profiles and pulsed-field gel electrophoresis (PFGE). Results: A high prevalence of multidrug-resistant isolates, mainly showing an ampicillin, nalidixic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…They consist of two species: Salmonella enterica and S. bongori , and so far, more than 2,500 serotypes have been reported. Salmonella Enteritidis and Salmonella Typhimurium are two major serotypes that cause food poisoning [ 3 , 8 , 9 , 10 ]. In addition, these strains cause food poisoning in both humans and animals as they have no specificity in terms of who can be infected with them and develop illness; in most cases, contaminated food, improper handling, and distribution of meat and inadequate cooking cause illness in humans [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…They consist of two species: Salmonella enterica and S. bongori , and so far, more than 2,500 serotypes have been reported. Salmonella Enteritidis and Salmonella Typhimurium are two major serotypes that cause food poisoning [ 3 , 8 , 9 , 10 ]. In addition, these strains cause food poisoning in both humans and animals as they have no specificity in terms of who can be infected with them and develop illness; in most cases, contaminated food, improper handling, and distribution of meat and inadequate cooking cause illness in humans [ 3 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to displaying high resistance rates to other b-lactam antimicrobials tested (ampicillin, cephalothin), Salmonella isolates were often frequently resistant to gentamicin, streptomycin, nalidixic acid, and tetracycline and may reflect consequences of use for both treatment and growth promotion in poultry production (DANMAP, 2011). Kweon et al (2014) also reported nearly the same resistance pattern (ampicillin, gentamicin, nalidixic acid, and tetracycline) in three CTX-M-15 Salmonella isolates in South Korea. A universal primer set for CTX-M groups was only one primer observed from all tested five bla genes.…”
Section: Resultsmentioning
confidence: 73%
“…In addition, the increasing risk of antimicrobial resistance in Salmonella isolates has been recognized. In Korea, CTX-M-15 extended-spectrum b-lactamase (ESBL)-producing Salmonella strains have been sporadically and limitedly isolated from clinical (Kweon et al, 2014), animal, and chicken meat samples (Tamang et al, 2011). Specifically, one of the most typical dispersal routes of antibioticresistant Salmonella is through poultry-derived food sources ( Jiang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%